Integration of Physical Pre-treatment with Enzymatic Hydrolysis of Sago Hampas for Maximising Reducing Sugar Recovery - Zakaria, Ismail (Universiti Malaysia Sarawak (UNIMAS), 2020)
Nowadays, the efficient utilization of agro-industrial by-products for conversion to a range of commercial value-added bio-products, including bio-ethanol, bio-fuels, and bio-material has been increased. Sago hampas contains significant amounts of starch (50% - 60%), cellulose (20% - 23%), hemicellulose (9.2%) and lignin (3.9%), hence able to be used as a substrate for generating reducing sugar. This research project focuses on the recovery of glucose from starchy sago hampas and reducing sugar from fibre of destarched sago hampas through incorporation of physical pre-treatment and enzymatic hydrolysis. The sago hampas was treated with selected physical pre-treatments such as hydrothermal, microwave and ultrasound, then subsequently proceed with boiling and enzymatic hydrolysis on starch residue for glucose production by using commercial liquefying and saccharifying enzymes. The percentage hydrolysis yield of glucose for selected pre-treatments were compared to identify the best pre-treatment that can be incorporated with enzymatic hydrolysis to maximise the glucose recovery. High Performance Liquid Chromatography was used to analyse and measure the concentration of glucose recovered from starch residue in sago hampas. Hydrothermal pre-treatment was identified as the best treatment to implement on starch residue whereby the percentage of hydrolysis yield was increased by approximately 6% compared to without pre-treatment. Meanwhile, the microwave and ultrasound pre-treatment also increased approximately 1.56% and 3.68% of hydrolysis yield respectively. The treated and untreated sago hampas were observed under scanning electron microscope to show the changes on physical structure of starch granules and cellulosic materials. Observations revealed that there was a change in the physical structure of the starch granules in which there were a lot of deep holes on the surface, even some of them were ruptured. The hydrothermal pre-treatment was chosen to treat the destarched sago hampas and subsequently hydrolysed through enzymatic hydrolysis by using cellulase and β-glucosidase enzymes. The optimum substrate loading, enzyme dosage (beta-glucosidase) and incubation time were identified by measuring the optimum concentration of reducing sugar yield and percentage of hydrolysis yield. Five percent substrate loading (w/v) of destarched sago hampas, 5% (v/w) enzyme dosage of β-glucosidase enzyme and 48 h of incubation time were identified as optimum parameter to hydrolyse the treated destarched sago hampas. Keyword: Sago hampas, starch, cellulosic materials, physical pre-treatment, enzymatic hydrolysis.